Christ For Us Today – Promeity in the Christologies of Bonhoeffer and Kierkegaard. (12th November 2012) - Ziegler, Philip
Abstract In 1944, Bonhoeffer famously asked 'Who is Christ really, for us today?' This question is ambiguous: 'Christ for us' points to an objective claim concerning the personal identity of Christ, while 'for us today' signals the need for ever new subjective value judgements and contextual appropriations. Does emphasis upon the promeity of Christ, like that found in the work of Bonhoeffer, volatilize the identity of Christ? Examination of the theme of promeity in the work of Bonhoeffer himself, as well as that of Kierkegaard, demonstrates that in the hands of both these Lutheran theologians promeity is acknowledged to be intrinsic to the fides quae creditur. The subjective appropriation and contextual character of Christology then proves to be a function of a prior and more decisive reality, namely the very identity of God in Christ for us.